Cutaneous dysbiosis may amplify barrier dysfunction in patients with atopic dermatitis - Hammond, Margaret; Gamal, Ahmed; Mukherjee, Pranab K.; Damiani, Giovanni; McCormick, Thomas S.; Ghannoum, Mahmoud A.; Nedorost, Susan (Frontiers in Microbiology, 2022)
Atopic dermatitis (AD) was recently associated with cutaneous dysbiosis, barrier defects, and immune dysregulation but their single contribution, as well their interaction in determine AD flares remains still unknown. Early-onset barrier dysfunction may cause an innate immune response to commensal organisms and, consequently, the development of different allergies. We aimed to compare the cutaneous microbiome in atopic dermatitis patients Vs non-atopic ones. Next-gen Ion-Torrent deep-sequencing identified AD-associated changes in the skin bacterial microbiome (“bacteriome”) and fungal microbiome (“mycobiome”) of atopic and non-atopic patients. Data were analysed for diversity, abundance and inter-kingdom correlations. Microbial interactions were assessed in biofilms using metabolic activity (XTT) assay and scanning electron microscopy (SEM), while host-pathogen interactions were determined in cultured primary keratinocytes exposed to biofilms. Increased richness and abundance of Staphylococcus, Lactococcus and Alternaria were found in atopics. Staphylococcus and Alternaria formed robust mixed-species biofilms (based on XTT and SEM) that were resistant to antifungals/antimicrobials. Furthermore, their biofilm supernatant was capable to influence keratinocytes biology (pro-inflammatory cytokines and structural proteins), suggesting a additive effect on AD-associated host response. In conclusion, microbial inter-kingdom and host-microbiome interactions may play critical role in modulation of atopic dermatitis.